Efficacy and immunogenicity of R21/Matrix-M vaccine against clinical malaria after 2 years' follow-up in children in Burkina Faso: a phase 1/2b randomised controlled trial. Issue 12 (December 2022) - Datoo, Mehreen S; Natama, Hamtandi Magloire; Somé, Athanase; Bellamy, Duncan; Traoré, Ousmane; Rouamba, Toussaint; Tahita, Marc Christian; Ido, N Félix André; Yameogo, Prisca; Valia, Daniel; Millogo, Aida; Ouedraogo, Florence; et al.
Summary: Background: Malaria is a leading cause of morbidity and mortality worldwide. We previously reported the efficacy of the R21/Matrix-M malaria vaccine, which reached the WHO-specified goal of 75% or greater efficacy over 12 months in the target population of African children. Here, we report the safety, immunogenicity, and efficacy results at 12 months following administration of a booster vaccination. Methods: This double-blind phase 1/2b randomised controlled trial was done in children aged 5–17 months in Nanoro, Burkina Faso. Eligible children were enrolled and randomly assigned (1:1:1) to receive three vaccinations of either 5 μg R21/25 μg Matrix-M, 5 μg R21/50 μg Matrix-M, or a control vaccine (the Rabivax-S rabies vaccine) before the malaria season, with a booster dose 12 months later. Children were eligible for inclusion if written informed consent could be provided by a parent or guardian. Exclusion criteria included any existing clinically significant comorbidity or receipt of other investigational products. A random allocation list was generated by an independent statistician by use of block randomisation with variable block sizes. A research assistant from the University of Oxford, independent of the trial team, prepared sealed envelopes using this list, which was then provided to the study pharmacists to assign participants. All vaccines were prepared by the study pharmacists by use of the same type of syringe, and the contents were covered with an opaque label. Vaccine safety, efficacy, and a potential correlate of efficacy with immunogenicity, measured as anti-NANP antibody titres, were evaluated over 1 year following the first booster vaccination. The population in which the efficacy analyses were done comprised all participants who received the primary series of vaccinations and a booster vaccination. Participants were excluded from the efficacy analysis if they withdrew from the trial within the first 2 weeks of receiving the booster vaccine. This trial is registered with ClinicalTrials.gov (NCT03896724 ), and is continuing for a further 2 years to assess both the potential value of additional booster vaccine doses and longer-term safety. Findings: Between June 2, and July 2, 2020, 409 children returned to receive a booster vaccine. Each child received the same vaccination for the booster as they received in the primary series of vaccinations; 132 participants received 5 μg R21 adjuvanted with 25 μg Matrix-M, 137 received 5 μg R21 adjuvanted with 50 μg Matrix-M, and 140 received the control vaccine. R21/Matrix-M had a favourable safety profile and was well tolerated. Vaccine efficacy remained high in the high adjuvant dose (50 μg) group, similar to previous findings at 1 year after the primary series of vaccinations. Following the booster vaccination, 67 (51%) of 132 children who received R21/Matrix-M with low-dose adjuvant, 54 (39%) of 137 children who received R21/Matrix-M with high-dose adjuvant, and 121 (86%) of 140 children who received the rabies vaccine developed clinical malaria by 12 months. Vaccine efficacy was 71% (95% CI 60 to 78) in the low-dose adjuvant group and 80% (72 to 85) in the high-dose adjuvant group. In the high-dose adjuvant group, vaccine efficacy against multiple episodes of malaria was 78% (95% CI 71 to 83), and 2285 (95% CI 1911 to 2568) cases of malaria were averted per 1000 child-years at risk among vaccinated children in the second year of follow-up. Among these participants, at 28 days following their last R21/Matrix-M vaccination, titres of malaria-specific anti-NANP antibodies correlated positively with protection against malaria in both the first year of follow-up (Spearman's ρ –0·32 [95% CI –0·45 to –0·19]; p=0·0001) and second year of follow-up (–0·20 [–0·34 to –0·06]; p=0·02). Interpretation: A booster dose of R21/Matrix-M at 1 year following the primary three-dose regimen maintained high efficacy against first and multiple episodes of clinical malaria. Furthermore, the booster vaccine induced antibody concentrations that correlated with vaccine efficacy. The trial is ongoing to assess long-term follow-up of these participants and the value of further booster vaccinations. Funding: European and Developing Countries Clinical Trials Partnership 2 (EDCTP2), Wellcome Trust, and NIHR Oxford Biomedical Research Centre. Translation: For the French translation of the abstract see Supplementary Materials section.